Method for producing conductive polymer dispersion and method for producing capacitor
The method of manufacturing a conductive polymer dispersion with a polyanion and polyol compound addresses the viscosity and ESR issues in capacitors, resulting in improved performance and stability under high temperatures.
Patent Information
- Application Number
- JP2023106850
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-17
AI Technical Summary
Conductive polymer dispersions used in capacitors require low viscosity to penetrate porous dielectric layers and prevent increases in equivalent series resistance (ESR) under high temperatures.
A method for manufacturing a conductive polymer dispersion by polymerizing a π-conjugated conductive polymer with a polyanion and a specific polyol compound in an aqueous medium, ensuring a low viscosity and stable ESR through controlled polymerization and composition.
The resulting conductive polymer dispersion achieves low viscosity and reduced ESR, enhancing capacitor performance with improved heat resistance and stability.
Smart Images

Figure 2025006202000002 
Figure 2025006202000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a conductive polymer dispersion containing a π-conjugated conductive polymer and a polyanion, and a method for producing a capacitor. [Background technology]
[0002] A π-conjugated conductive polymer, whose main chain is composed of a π-conjugated system, forms a conductive complex by doping with a polyanion having an anionic group, and becomes dispersible in water. A method for manufacturing a capacitor has been disclosed in which a paint made of a conductive polymer dispersion liquid containing a conductive complex is applied to a dielectric layer provided on the surface of an anode made of a valve metal, the paint is dried to form a solid electrolyte layer, and a cathode is placed opposite the solid electrolyte layer (for example, Patent Document 1). According to this disclosure, the performance of the capacitor is improved by adding a specific unsaturated aliphatic alcohol compound to the paint. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2022-071400 Summary of the Invention [Problem to be solved by the invention]
[0004] The conductive polymer dispersion used in the production of the capacitor is required to have a low viscosity in order to permeate the porous structure of the dielectric layer. In addition, capacitors equipped with a solid electrolyte layer, which is a hardened product of a conventional conductive polymer dispersion, have a problem in that the equivalent series resistance (ESR) increases when exposed to high temperatures for a long period of time. This increase in ESR leads to deterioration of the performance of the capacitor, so improvements were required.
[0005] The present invention provides a method for producing a conductive polymer dispersion having a low viscosity, and a method for producing a capacitor having a solid electrolyte layer made of a cured product of the conductive polymer dispersion. [Means for solving the problem]
[0006] [1] A method for producing a conductive polymer dispersion, comprising polymerizing a monomer that forms a π-conjugated conductive polymer in a reaction liquid containing a polyanion, a specific polyol compound, and an aqueous dispersion medium, to obtain a conductive polymer dispersion containing a conductive complex containing the π-conjugated conductive polymer and the polyanion, and the polyol compound, wherein the polyol compound has one or more linear or branched alkylene groups having 2 to 6 carbon atoms and 2 to 3 hydroxyl groups in the molecule. [2] The method for producing a conductive polymer dispersion according to [1], wherein the content of water in the aqueous dispersion medium is 70 mass % or more based on the total mass of the aqueous dispersion medium. [3] The method for producing a conductive polymer dispersion according to [2], wherein the π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene), or the polyanion is polystyrenesulfonic acid, or the π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene) and the polyanion is polystyrenesulfonic acid. [4] The method for producing a conductive polymer dispersion according to [3], wherein the polyol compound is one or more selected from the group consisting of ethylene glycol, diethylene glycol, triethylene glycol, and propylene glycol. [5] The method for producing a conductive polymer dispersion according to [1], wherein the content of the polyol compound relative to the total mass of the reaction liquid is 0.01 mass % or more and 0.50 mass % or less. [6] The method for producing a conductive polymer dispersion according to [5], wherein a content of the polyol compound per 100 parts by mass of the polyanion contained in the reaction liquid is 1 part by mass or more and 100 parts by mass or less. [7] The method for producing a conductive polymer dispersion according to [6], wherein a content of the polyol compound per 100 parts by mass of the monomer contained in the reaction liquid is 1 part by mass or more and 100 parts by mass or less. [8] A method for producing a capacitor, comprising the steps of obtaining a conductive polymer dispersion by the production method according to any one of [1] to [7], and applying the conductive polymer dispersion to a surface of a dielectric layer formed on a surface of an anode made of a porous valve metal, and drying the applied conductive polymer dispersion to form a solid electrolyte layer. [9] The method for producing a capacitor according to [8], wherein the content of the polyol compound per 100 parts by mass of the polyanion contained in the solid electrolyte layer is 200 parts by mass or more and 1,500 parts by mass or less.
[10] The method for producing a capacitor according to [9], wherein a content of the polyol compound per 100 parts by mass of the π-conjugated conductive polymer contained in the solid electrolyte layer is 500 parts by mass or more and 3,000 parts by mass or less. Effect of the Invention
[0007] The conductive polymer dispersion obtained by the manufacturing method of the present invention has a low viscosity and is therefore suitable for manufacturing a capacitor. Furthermore, the capacitor obtained by the manufacturing method of the present invention has a solid electrolyte layer made of a cured product of the conductive polymer dispersion, and therefore has a low ESR and excellent heat resistance.
[0008] This invention is believed to contribute to SDGs Goal 12, "Responsible Consumption and Production."
[0009] In this specification and claims, the lower limit and upper limit of a numerical range indicated with "to" are included in the numerical range. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 is a cross-sectional view illustrating one embodiment of a capacitor. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] <Method for producing conductive polymer dispersion> A first aspect of the present invention is a method for producing a conductive polymer dispersion, comprising polymerizing a monomer that forms a π-conjugated conductive polymer in a reaction liquid containing a polyanion, a specific polyol compound, and an aqueous dispersion medium, to obtain a conductive polymer dispersion containing a conductive complex containing the π-conjugated conductive polymer and the polyanion, and the polyol compound.
[0012] By forming the conductive complex in the presence of a specific polyol compound, it is possible to obtain a conductive polymer dispersion having low viscosity and suitable for producing a high-performance capacitor. According to this embodiment, the conductive polymer dispersion of the second embodiment can be produced.
[0013] <Preparation of polyanions> The polyanion used in the polymerization step of the monomer can be prepared by a conventional method, for example, by adding a polymerization initiator to a reaction solution containing a polymerizable anionic monomer and water to obtain an aqueous solution containing a polyanion formed by polymerization of the polymerizable anionic monomer.
[0014] The polymerizable anionic monomer is an organic compound that forms a polyanion upon polymerization and has at least one anionic group in one molecule. The anionic group is a functional group that can be ionized in water and may form a salt with a cation such as sodium or potassium. The polymerizable anionic monomer used in this step is preferably one or more selected from known monomers capable of forming a polyanion, which will be described in detail later. Among them, styrenesulfonic acid or a salt thereof capable of forming polystyrenesulfonic acid, which is particularly excellent as a dopant for π-conjugated conductive polymers, is most preferred.
[0015] The amount of the polymerizable anionic monomer to be mixed relative to the total mass of the reaction liquid is, for example, preferably from 1.0 to 25.0 mass %, more preferably from 10.0 to 20.0 mass %, and further preferably from 12.0 to 18.0 mass %.
[0016] Examples of the polymerization initiator include persulfates such as ammonium persulfate, sodium persulfate, and potassium persulfate. The amount of the polymerization initiator to be added relative to the total mass of the reaction liquid is, for example, 0.01 to 0.50% by mass.
[0017] The end of the polymerization reaction of the polyanion in the reaction solution is determined when the polymerization initiator added to the reaction solution is completely consumed. For example, when the reaction is carried out at 70 to 95° C. with stirring, the reaction may be completed in about 4 to 12 hours.
[0018] When the anion group of the polyanion obtained above forms a salt with a counter cation, it is preferable to remove the cation by contacting the polyanion with a cation exchange resin.
[0019] <Polymerization process> A π-conjugated conductive polymer is formed by polymerization reaction in a reaction solution containing a polyanion, a specific polyol compound, and an aqueous dispersion medium to obtain a conductive complex. For example, a specific polyol compound, a polymerizable monomer that forms a π-conjugated conductive polymer, and an arbitrary radical polymerization initiator are added to an aqueous polyanion solution to form the π-conjugated conductive polymer, thereby obtaining a dispersion of a conductive complex in which the π-conjugated conductive polymer and the polyanion are complexed. In the polymerization step, the π-conjugated conductive polymer is polymerized in the presence of a polyanion and a specific polyol compound, and other steps can be carried out by known methods.
[0020] (dispersion medium) The dispersion medium constituting the reaction liquid is preferably an aqueous dispersion medium containing water since the polyanion and the polyol compound are hydrophilic, but may contain a dispersion medium other than water. The conductive complex formed has excess anion groups derived from the polyanion and has high dispersibility in water, so the dispersion medium other than water is preferably a water-soluble organic solvent. Here, the water-soluble organic solvent is an organic solvent that dissolves in an amount of 1 g or more in 100 g of water at 20°C, and examples of the water-soluble organic solvent include alcohol-based solvents, ketone-based solvents, and ester-based solvents. The water-soluble organic solvent contained as the dispersion medium may be one type or two or more types.
[0021] Examples of alcohol-based solvents include methanol, ethanol, 1-propanol, 2-propanol (isopropanol), 2-methyl-2-propanol, 1-butanol, 2-butanol, 2-methyl-1-propanol, allyl alcohol, ethylene glycol, propylene glycol, propylene glycol monomethyl ether, and ethylene glycol monomethyl ether. Examples of the ether solvent include diethyl ether, dimethyl ether, propylene glycol dialkyl ether, and diethylene glycol diethyl ether. Examples of the ketone solvent include diethyl ketone, methyl propyl ketone, methyl butyl ketone, methyl isopropyl ketone, methyl isobutyl ketone, methyl amyl ketone, diisopropyl ketone, methyl ethyl ketone, acetone, and diacetone alcohol. Examples of the nitrogen atom-containing solvent include N-methylpyrrolidone, dimethylacetamide, and dimethylformamide. The water-soluble organic solvent may be contained alone or in combination of two or more kinds.
[0022] The content of water relative to the total mass of the dispersion medium excluding the solid content (non-volatile components) in the reaction liquid is preferably 70 mass% or more, more preferably 80 mass% or more, and even more preferably 90 mass% or more, and may be 100 mass%. The remainder is preferably a water-soluble organic solvent. When the water content is equal to or greater than the lower limit, the dispersibility of the formed conductive composite is increased.
[0023] The content of the polyol compound relative to the total mass of the reaction solution during the polymerization reaction is, for example, preferably from 0.01% by mass to 0.5% by mass, more preferably from 0.05% by mass to 1.0% by mass, and even more preferably from 0.10% by mass to 0.50% by mass. When the content is equal to or greater than the lower limit, the viscosity of the conductive polymer dispersion liquid formed can be made smaller. When the content is equal to or less than the upper limit, the amount of excess polyol compound contained in the conductive polymer dispersion liquid obtained can be reduced.
[0024] The content of the polyol compound relative to 100 parts by mass of the polyanion contained in the reaction liquid is, for example, 1 part by mass or more and 100 parts by mass or less, preferably 10 parts by mass or more and 100 parts by mass or less, more preferably 20 parts by mass or more and 80 parts by mass or less, and even more preferably 30 parts by mass or more and 60 parts by mass or less. When the content is equal to or greater than the lower limit, the viscosity of the conductive polymer dispersion liquid formed can be made smaller. When the content is equal to or less than the upper limit, the amount of excess polyol compound contained in the conductive polymer dispersion liquid obtained can be reduced.
[0025] The content of the polyol compound relative to 100 parts by mass of the monomer contained in the reaction liquid is, for example, 1 part by mass or more and 100 parts by mass or less, preferably 10 parts by mass or more and 200 parts by mass or less, more preferably 20 parts by mass or more and 150 parts by mass or less, even more preferably 30 parts by mass or more and 120 parts by mass or less, and particularly preferably 60 parts by mass or more and 100 parts by mass or less. When the content is equal to or greater than the lower limit, the viscosity of the conductive polymer dispersion liquid formed can be made smaller. When the content is equal to or less than the upper limit, the amount of excess polyol compound contained in the conductive polymer dispersion liquid obtained can be reduced.
[0026] The polyol compound is preferably one or more selected from the group described later in detail, and among them, one or more selected from ethylene glycol, diethylene glycol, triethylene glycol, and propylene glycol are most preferable because a conductive polymer dispersion liquid with lower viscosity can be obtained and a solid electrolyte layer with low ESR and high heat resistance can be formed when a capacitor is constructed.
[0027] The polymerizable monomer forming the π-conjugated conductive polymer is preferably one or more selected from known monomers capable of forming the π-conjugated conductive polymer described later in detail. Among them, 3,4-ethylenedioxythiophene capable of forming PEDOT having excellent conductivity and heat resistance is the most preferable.
[0028] The amount of the monomer to be mixed relative to the total mass of the reaction liquid is, for example, preferably from 0.01% by mass to 2.0% by mass, more preferably from 0.1% by mass to 1.0% by mass, and even more preferably from 0.4% by mass to 0.7% by mass. The amount of the polyanion relative to the total mass of the reaction solution is, for example, preferably 0.1% by mass to 3.0% by mass, more preferably 0.5% by mass to 2.0% by mass, and even more preferably 1.0% by mass to 1.5% by mass. By setting the content within the above preferred range, a conductive polymer dispersion having the conductive complex concentration in the above preferred content can be easily obtained.
[0029] Examples of the radical polymerization initiator include persulfates such as ammonium persulfate, sodium persulfate, potassium persulfate, etc. It is preferable to add a catalyst such as a transition metal compound such as ferric chloride, ferric sulfate, ferric nitrate, cupric chloride, etc., to the reaction liquid together with the radical polymerization initiator.
[0030] The amount of the radical polymerization initiator to be mixed relative to the total mass of the reaction solution during the polymerization reaction is, for example, preferably from 0.10% by mass to 1.00% by mass, more preferably from 0.30% by mass to 0.80% by mass, and even more preferably from 0.50% by mass to 0.70% by mass.
[0031] The reaction temperature in the reaction solution can be, for example, 20 to 30°C. At the above reaction temperature, the polymerization reaction is usually completed in about 4 to 12 hours. The end of the polymerization reaction can be determined by measuring the amount of unreacted monomer in the reaction solution by gas chromatography or the like. After the polymerization reaction, the reaction solution containing the conductive complex is obtained as a conductive polymer dispersion.
[0032] It is preferable to remove residues of the catalyst and radical polymerization initiator added to the reaction liquid from the conductive polymer dispersion after the polymerization reaction. Examples of the removal method include a method of contacting the conductive polymer dispersion with an ion exchange resin to adsorb the catalyst and radical polymerization initiator to the ion exchange resin, and a method of ultrafiltrating the conductive polymer dispersion to replace the dispersion medium and remove the catalyst and radical polymerization initiator. Among these, the method using an ion exchange resin is preferable because it is simple. It is preferable to use a cation exchange resin and an anion exchange resin in combination as the ion exchange resin.
[0033] The obtained conductive polymer dispersion may be subjected to a dispersion treatment by a conventional method such as using a high-pressure homogenizer.
[0034] A polyol compound, a nitrogen-containing aromatic compound, any additives, etc. may be further added to the conductive polymer dispersion liquid obtained above.
[0035] ≪Conductive polymer dispersion liquid≫ A second aspect of the present invention is a conductive polymer dispersion liquid comprising a conductive complex containing a π-conjugated conductive polymer and a polyanion, a polyol compound, and an aqueous dispersion medium. The conductive polymer dispersion liquid of this aspect is preferably produced by the production method of the first aspect.
[0036] <Conductive composite> The conductive complex of this embodiment includes a π-conjugated conductive polymer and a polyanion. The polyanion in the conductive complex is doped into the π-conjugated conductive polymer to form a conductive complex having electrical conductivity. In the polyanion, only a part of the anionic groups is doped into the π-conjugated conductive polymer, and the polyanion has excess anionic groups that are not involved in the doping. Since the excess anionic groups are hydrophilic groups, the conductive complex has water dispersibility. When the number of all anionic groups in the polyanion is taken as 100 mol %, the excess anionic groups are preferably from 30 mol % to 90 mol %, more preferably from 45 mol % to 75 mol %.
[0037] (π-conjugated conductive polymer) The π-conjugated conductive polymer may be an organic polymer whose main chain is composed of a π-conjugated system, and examples thereof include polypyrrole-based conductive polymers, polythiophene-based conductive polymers, polyacetylene-based conductive polymers, polyphenylene-based conductive polymers, polyphenylenevinylene-based conductive polymers, polyaniline-based conductive polymers, polyacene-based conductive polymers, polythiophenevinylene-based conductive polymers, and copolymers thereof. From the viewpoint of stability in air, polypyrrole-based conductive polymers, polythiophenes, and polyaniline-based conductive polymers are preferred, and from the viewpoint of transparency, polythiophene-based conductive polymers are more preferred.
[0038] Polythiophene-based conductive polymers include polythiophene, poly(3-methylthiophene), poly(3-ethylthiophene), poly(3-propylthiophene), poly(3-butylthiophene), poly(3-hexylthiophene), poly(3-heptylthiophene), poly(3-octylthiophene), poly(3-decylthiophene), poly(3-dodecylthiophene), poly(3-octadecylthiophene), poly(3-bromothiophene), poly(3-chlorothiophene), and poly(3-iodothiophene). thiophene), poly(3-cyanothiophene), poly(3-phenylthiophene), poly(3,4-dimethylthiophene), poly(3,4-dibutylthiophene), poly(3-hydroxythiophene), poly(3-methoxythiophene), poly(3-ethoxythiophene), poly(3-butoxythiophene), poly(3-hexyloxythiophene), poly(3-heptyloxythiophene), poly(3-octyloxythiophene), poly(3-decyloxythiophene), poly(3-dodecyloxythiophene), oxythiophene), poly(3-octadecyloxythiophene), poly(3,4-dihydroxythiophene), poly(3,4-dimethoxythiophene), poly(3,4-diethoxythiophene), poly(3,4-dipropoxythiophene), poly(3,4-dibutoxythiophene), poly(3,4-dihexyloxythiophene), poly(3,4-diheptyloxythiophene), poly(3,4-dioctyloxythiophene), poly(3,4-didecyloxythiophene), poly(3,4-di dodecyloxythiophene), poly(3,4-ethylenedioxythiophene), poly(3,4-propylenedioxythiophene), poly(3,4-butylenedioxythiophene), poly(3-methyl-4-methoxythiophene), poly(3-methyl-4-ethoxythiophene), poly(3-carboxythiophene), poly(3-methyl-4-carboxythiophene), poly(3-methyl-4-carboxyethylthiophene), and poly(3-methyl-4-carboxybutylthiophene). Examples of polypyrrole-based conductive polymers include polypyrrole, poly(N-methylpyrrole), poly(3-methylpyrrole), poly(3-ethylpyrrole), poly(3-n-propylpyrrole), poly(3-butylpyrrole), poly(3-octylpyrrole), poly(3-decylpyrrole), poly(3-dodecylpyrrole), poly(3,4-dimethylpyrrole), poly(3,4-dibutylpyrrole), poly(3-carboxypyrrole), poly(3-methyl-4-carboxypyrrole), poly(3-methyl-4-carboxyethylpyrrole), poly(3-methyl-4-carboxybutylpyrrole), poly(3-hydroxypyrrole), poly(3-methoxypyrrole), poly(3-ethoxypyrrole), poly(3-butoxypyrrole), poly(3-hexyloxypyrrole), and poly(3-methyl-4-hexyloxypyrrole). Examples of polyaniline-based conductive polymers include polyaniline, poly(2-methylaniline), poly(3-isobutylaniline), poly(2-anilinesulfonic acid), and poly(3-anilinesulfonic acid). Among these π-conjugated conductive polymers, poly(3,4-ethylenedioxythiophene) is particularly preferable because of its excellent conductivity, transparency, and heat resistance. The conductive composite may contain one type of π-conjugated conductive polymer, or two or more types of polymers.
[0039] (Polyanion) A polyanion is a polymer having two or more monomer units each having an anionic group in the molecule. The anionic group of the polyanion functions as a dopant for a π-conjugated conductive polymer, improving the conductivity of the π-conjugated conductive polymer. The anion group of the polyanion is preferably a sulfo group or a carboxy group. Specific examples of such polyanions include polymers having a sulfo group, such as polystyrene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyacrylic acid esters having a sulfo group, polymethacrylic acid esters having a sulfo group (for example, poly(4-sulfobutyl methacrylate, polysulfoethyl methacrylate, polymethacryloyloxybenzenesulfonic acid), poly(2-acrylamido-2-methylpropanesulfonic acid), and polyisoprene sulfonic acid; and polymers having a carboxy group, such as polyvinyl carboxylic acid, polystyrene carboxylic acid, polyallyl carboxylic acid, polyacrylic acid, polymethacrylic acid, poly(2-acrylamido-2-methylpropanecarboxylic acid), and polyisoprene carboxylic acid. The polyanion may be a homopolymer in which a single monomer is polymerized, or a copolymer in which two or more monomers are polymerized. Among these polyanions, polymers having a sulfo group are preferred, and polystyrene sulfonic acid is more preferred, since they can provide higher electrical conductivity.
[0040] The weight average molecular weight Mw of the polyanion is preferably from 20,000 to 1,000,000, and more preferably from 50,000 to 800,000. The weight average molecular weight Mw is an average molecular weight based on mass measured by gel filtration chromatography and calculated as pullulan.
[0041] The content of the polyanion contained in the conductive composite of this embodiment is preferably, for example, 1 part by mass or more and 1000 parts by mass or less, more preferably 10 parts by mass or more and 700 parts by mass or less, and even more preferably 100 parts by mass or more and 500 parts by mass or less, relative to 100 parts by mass of the π-conjugated conductive polymer. If the content of the polyanion is equal to or more than the lower limit, the doping effect on the π-conjugated conductive polymer tends to be stronger, and the conductivity becomes higher. On the other hand, if the content of the polyanion is equal to or less than the upper limit, the content of the π-conjugated conductive polymer becomes sufficient, so that sufficient conductivity can be ensured.
[0042] The total content of the π-conjugated conductive polymer and the polyanion (i.e., the content of the conductive complex) relative to the total mass of the conductive polymer dispersion of this embodiment is preferably 0.1 mass% or more and 5.0 mass% or less, more preferably 0.5 mass% or more and 2.5 mass% or less, and even more preferably 0.8 mass% or more and 2.0 mass% or less. When the content is within the above preferred range, the dispersibility of the conductive composite is increased, improving the coatability, and the ESR of a capacitor having a solid electrolyte layer formed from the conductive polymer dispersion can be further reduced.
[0043] (Polyol compound 1) When the conductive polymer dispersion of this embodiment is formed by the manufacturing method of the first embodiment, the formation of the conductive composite is carried out in the presence of a specific polyol compound, so that the viscosity of the conductive composite is reduced. In addition, the ESR of a capacitor having a solid electrolyte layer formed from the conductive polymer dispersion can be further reduced, and the heat resistance of the capacitor can be improved.
[0044] From the viewpoint of fully obtaining the above-mentioned effects, the polyol compound preferably has one or more linear or branched alkylene groups having 2 to 6 carbon atoms in the molecule and has two to three hydroxyl groups, and is more preferably one or more selected from ethylene glycol, diethylene glycol, triethylene glycol, and propylene glycol.
[0045] The content of the polyol compound relative to the total mass of the conductive polymer dispersion immediately after polymerization of the above-mentioned π-conjugated conductive polymer is, for example, preferably from 0.01% by mass to 0.5% by mass, more preferably from 0.05% by mass to 1.0% by mass, and even more preferably from 0.10% by mass to 0.50% by mass. When the content is equal to or more than the lower limit, the viscosity of the conductive polymer dispersion can be further reduced, and the heat resistance of the solid electrolyte layer can be further improved. When the content is equal to or less than the upper limit, a decrease in the electrical conductivity of the solid electrolyte layer, which is the cured product, can be suppressed. When used in the production of a capacitor, a polyol compound may be further added to the conductive polymer dispersion liquid from the viewpoint of increasing the conductivity of the solid electrolyte layer and reducing the ESR.
[0046] (dispersion medium) The dispersion medium contained in the conductive polymer dispersion is an aqueous dispersion medium containing water because the conductive complex is hydrophilic. Also, a dispersion medium other than water may be contained. The dispersion medium other than water is not particularly limited as long as it does not significantly impair the dispersibility of the conductive complex. Since the conductive complex has excess anion groups derived from the polyanion and has high dispersibility in water, the dispersion medium other than water is preferably a water-soluble organic solvent. The water-soluble organic solvent contained as the dispersion medium may be one type or two or more types.
[0047] The content of water relative to the total mass of the dispersion medium excluding the solid content (non-volatile components) of the conductive polymer dispersion is preferably 70 mass% or more, more preferably 80 mass% or more, even more preferably 90 mass% or more, and may be 100 mass%. When the water content is equal to or more than the above lower limit, the dispersibility of the conductive complex contained in the conductive polymer dispersion is increased, and the coatability is improved. In addition, the ESR of a capacitor having a solid electrolyte layer formed from the conductive polymer dispersion can be further reduced. In addition, the antistatic properties of a conductive laminate having a conductive layer formed from the conductive polymer dispersion can be further improved.
[0048] The viscosity of the conductive polymer dispersion at 25° C., when the concentration of the conductive complex relative to the total mass of the conductive polymer dispersion is adjusted to 1.6 mass %, is preferably 40 mPa·s or less, more preferably 30 mPa·s or less, even more preferably 20 mPa·s or less, and particularly preferably 13 mPa·s or less. There is no particular lower limit to the viscosity, and a guideline is 1 mPa·s or more. In the measurement of the viscosity, the dispersion medium contained in the conductive polymer dispersion is preferably ion-exchanged water alone. Furthermore, the conductive polymer dispersion for which the viscosity is measured contains the polyol compound, but preferably does not contain any other additives. The viscosity was measured at 25° C. using a tuning fork vibration viscometer in accordance with JIS Z8803:2011 (viscosity measurement method using a vibration viscometer).
[0049] (Polyol compound 2) One or more polyol compounds may be added to the conductive polymer dispersion after the polymerization. Here, the polyol compound refers to a compound having two or more hydroxyl groups, which is different from the π-conjugated conductive polymer and the polyanion. By including the polyol compound, the ESR of a capacitor having a solid electrolyte layer formed from the conductive polymer dispersion can be further reduced.
[0050] Examples of the polyol compound include one or more selected from ethylene glycol, diethylene glycol, propylene glycol, 1,4-butanediol, glycerin, and polyethylene glycol. The polyol compound added after the polymerization may be the same as or different from the polyol compound blended in the polymerization reaction liquid.
[0051] The content of the polyol compound contained in the conductive polymer dispersion is, for example, preferably 100 parts by mass or more and 5000 parts by mass or less, more preferably 200 parts by mass or more and 2000 parts by mass or less, and even more preferably 300 parts by mass or more and 1000 parts by mass or less, relative to 100 parts by mass in total of the π-conjugated conductive polymer and the polyanion. When it is in the above suitable range, the coatability of the conductive polymer dispersion is improved, and the ESR of the capacitor can be further reduced.
[0052] The content of the polyol compound relative to the total mass of the conductive polymer dispersion is preferably from 1% by mass to 20% by mass, more preferably from 3% by mass to 15% by mass, and even more preferably from 5% by mass to 10% by mass. When it is in the above preferred range, the coatability of the conductive polymer dispersion is improved, and the ESR of the capacitor can be further reduced.
[0053] (Nitrogen-containing aromatic compounds) The conductive polymer dispersion may contain one or more nitrogen-containing aromatic compounds. Here, the nitrogen-containing aromatic compound refers to an aromatic compound in which at least one nitrogen atom forms a ring structure. By containing the nitrogen-containing aromatic compound, the ESR of the capacitor having a solid electrolyte layer formed from the conductive polymer dispersion can be further reduced.
[0054] Examples of the nitrogen-containing aromatic compounds include pyrrole, indole, imidazole, 2-methylimidazole, 2-propylimidazole, N-methylimidazole, N-propylimidazole, N-butylimidazole, 1-(2-hydroxyethyl)imidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 1-benzyl-2-methylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 2-phenyl-4, Examples of the derivatives include 5-dihydroxymethylimidazole, 1-acetylimidazole, 2-aminobenzimidazole, 2-amino-1-methylbenzimidazole, 2-hydroxybenzimidazole, 2-(2-pyridyl)benzimidazole, pyridine, pyrimidine, pyrazine, and derivatives thereof such as alkyl-substituted derivatives (e.g., substituted derivatives with an alkyl group having 1 to 4 carbon atoms, such as methyl, ethyl, propyl, butyl, etc.), halogen-substituted derivatives (e.g., substituted derivatives with a halogen group, such as fluoro, chloro, bromine, etc.), and nitrile-substituted derivatives. Among these, imidazole is more preferable.
[0055] The content of the nitrogen-containing aromatic compound in the conductive polymer dispersion is preferably, for example, 1 part by mass or more and 100 parts by mass or less relative to 100 parts by mass in total of the π-conjugated conductive polymer and the polyanion. When it is in the above preferred range, the ESR of the capacitor can be further reduced.
[0056] The content of the nitrogen-containing aromatic compound relative to the total mass of the conductive polymer dispersion is preferably 0.01% by mass or more and 1.0% by mass or less. When it is in this preferred range, the ESR of the capacitor can be further reduced.
[0057] (Optional Additives) The conductive polymer dispersion of this embodiment may contain any additive other than the conductive complex within the scope of the present invention, and the content ratio is appropriately determined depending on the type of additive, but can be, for example, 1 to 1000 parts by mass per 100 parts by mass of the total of the π-conjugated conductive polymer and the polyanion. Here, the optional additive is a compound other than the polyol compound and the dispersion medium.
[0058] Examples of the optional additives include a surfactant, an inorganic conductive agent, an antifoaming agent, a coupling agent, an antioxidant, and an ultraviolet absorbing agent. The surfactant may be a nonionic, anionic or cationic surfactant, with the nonionic surfactant being preferred from the standpoint of storage stability. Polymer surfactants such as polyvinyl alcohol and polyvinylpyrrolidone may also be added. Examples of the inorganic conductive agent include metal ions, conductive carbon, etc. Metal ions can be generated by dissolving a metal salt in water. The antifoaming agent includes silicone resin, polydimethylsiloxane, silicone oil, and the like. The coupling agent may be a silane coupling agent having a vinyl group, an amino group, an epoxy group, or the like. Examples of the antioxidant include phenol-based antioxidants, amine-based antioxidants, phosphorus-based antioxidants, sulfur-based antioxidants, and sugars. Examples of the ultraviolet absorber include benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, salicylate-based ultraviolet absorbers, cyanoacrylate-based ultraviolet absorbers, oxanilide-based ultraviolet absorbers, hindered amine-based ultraviolet absorbers, and benzoate-based ultraviolet absorbers.
[0059] <Method for manufacturing conductive laminate> The conductive laminate can be produced by a production method including a step of applying the conductive polymer dispersion according to the second aspect of the present invention to at least a partial surface of a substrate to form a conductive layer.
[0060] Examples of a method for applying (coating) the conductive polymer dispersion on an arbitrary surface of a substrate include a method using a coater such as a gravure coater, a roll coater, a curtain flow coater, a spin coater, a bar coater, a reverse coater, a kiss coater, a fountain coater, a rod coater, an air doctor coater, a knife coater, a blade coater, a cast coater, or a screen coater; a method using a sprayer such as an air spray, an airless spray, or a rotor dampening; and an immersion method such as dipping.
[0061] The amount of the conductive polymer dispersion applied to the substrate is not particularly limited, but may be, for example, 0.01 to 10.0 g / m as a non-volatile component. 2 The range is preferably:
[0062] The conductive layer can be formed by drying the coating film made of the conductive polymer dispersion applied onto the substrate to remove at least a portion of the dispersion medium and curing the coating film. Methods for drying the coating film include heat drying, vacuum drying, etc. Examples of heat drying that can be used include hot air heating and infrared heating. When applying heat drying, the heating temperature is appropriately set depending on the dispersion medium used, but is usually within the range of 50° C. to 200° C. Here, the heating temperature is the set temperature of the drying device. A suitable drying time within the above heating temperature range is preferably 0.5 minutes to 30 minutes, more preferably 1 minute to 15 minutes.
[0063] <Conductive laminate> The conductive laminate comprises a substrate and a conductive layer formed on at least a portion of the surface of the substrate, and the conductive layer contains a cured product of the conductive polymer dispersion of the second aspect.
[0064] [Conductive layer] The conductive layer may be formed over the entire surface of any surface of the substrate, or over a portion of the entire surface. In the conductive film, it is preferable that a conductive layer of substantially uniform thickness is formed over substantially the entire surface of one surface or the other surface of the film substrate. When a conductive layer is formed only over a portion of the surface of the substrate, the conductive layer may be, for example, a fine conductive pattern such as a circuit or an electrode, or the conductive layer may be provided on the same surface and the conductive layer may be not provided on the same surface and may be roughly divided.
[0065] The average thickness of the conductive layer is, for example, preferably 10 nm or more and 100 μm or less, more preferably 20 nm or more and 50 μm or less, and even more preferably 30 nm or more and 30 μm or less. When the average thickness of the conductive layer is equal to or greater than the lower limit, high conductivity can be exhibited, and when the average thickness is equal to or less than the upper limit, the adhesion of the conductive layer to the substrate is further improved.
[0066] [Base material] The substrate may be a substrate made of an insulating material or a substrate made of a conductive material. The shape of the substrate is not particularly limited, and examples thereof include a shape mainly having a flat surface, such as a film or a substrate. Examples of insulating materials include glass, synthetic resin, and ceramics. The conductive material may be a metal, a conductive metal oxide, carbon, or the like.
[0067] (Film substrate) When a film substrate is used as the substrate, the conductive laminate becomes a conductive film. The film substrate may be, for example, a plastic film made of a synthetic resin, such as ethylene-methyl methacrylate copolymer resin, ethylene-vinyl acetate copolymer resin, polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinyl alcohol, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyacrylate, polycarbonate, polyvinylidene fluoride, polyarylate, styrene-based elastomer, polyester-based elastomer, polyethersulfone, polyetherimide, polyetheretherketone, polyphenylene sulfide, polyimide, cellulose triacetate, cellulose acetate propionate, etc. From the viewpoint of improving the adhesion between the film substrate and the conductive layer, the synthetic resin for the film substrate is preferably a polyester resin, and among these, polyethylene terephthalate is preferable.
[0068] The synthetic resin for the film substrate may be either amorphous or crystalline. The film substrate may be either unstretched or stretched. The film substrate may be subjected to a surface treatment such as a corona discharge treatment, a plasma treatment, or a flame treatment in order to further improve the adhesion of the conductive layer.
[0069] The average thickness of the film substrate is preferably 5 μm to 500 μm, more preferably 20 μm to 200 μm. If the average thickness of the film substrate is equal to or more than the lower limit, the film is less likely to break, and if the average thickness is equal to or less than the upper limit, the film can have sufficient flexibility. The average thickness of the film substrate is calculated by measuring the thickness at 10 randomly selected points and averaging the measured values.
[0070] (Glass substrate) Examples of the glass substrate include an alkali-free glass substrate, a soda-lime glass substrate, a borosilicate glass substrate, and a quartz glass substrate. If the substrate contains an alkali component, the conductivity of the conductive layer tends to decrease, so among the above glass substrates, an alkali-free glass is preferred. Here, the alkali-free glass refers to a glass composition in which the content of the alkali component is 0.1 mass% or less with respect to the total mass of the glass composition.
[0071] The average thickness of the glass substrate is preferably from 100 μm to 3000 μm, more preferably from 100 μm to 1000 μm. If the average thickness of the glass substrate is equal to or more than the lower limit, the substrate is less likely to break, and if the average thickness is equal to or less than the upper limit, the substrate can contribute to a thinner conductive laminate. The average thickness of the glass substrate is calculated by measuring the thickness at 10 randomly selected points and averaging the measured values.
[0072] <Capacitor manufacturing method> A capacitor can be manufactured by a manufacturing method including a step of applying the conductive polymer dispersion of the second aspect to the surface of a dielectric layer formed on the surface of an anode made of a porous valve metal, and drying the applied conductive polymer dispersion to form a solid electrolyte layer.
[0073] The method for manufacturing a capacitor preferably includes a step of oxidizing the surface of an anode made of a porous valve metal to form a dielectric layer (dielectric forming step), a step of arranging a cathode in a position facing the dielectric layer (cathode forming step), and a step of forming a solid electrolyte layer on at least a part of the surface of the dielectric layer (film forming step). Each step will be described below with reference to FIG.
[0074] [Dielectric formation process] In this step, the surface of anode 11 made of a porous valve metal is oxidized to form dielectric layer 12. The method for forming dielectric layer 12 is not particularly limited, and examples thereof include a method in which the surface of anode 11 is anodized in an electrolyte for chemical conversion treatment, such as an aqueous solution of ammonium adipate, an aqueous solution of ammonium borate, or an aqueous solution of ammonium phosphate.
[0075] [Cathode formation process] In this step, the cathode 13 is disposed at a position facing the dielectric layer 12. The method for disposing the cathode 13 is not particularly limited, and examples thereof include a method of forming the cathode 13 using a conductive paste such as a carbon paste or a silver paste, and a method of disposing a metal foil such as an aluminum foil facing the dielectric layer 12.
[0076] [Film forming process] In this step, the conductive polymer dispersion liquid described above is applied to at least a portion of the surface of the dielectric layer 12, and then dried to form the solid electrolyte layer 14.
[0077] Examples of the conductive polymer dispersion coating method include immersion (dip coating), comma coating, reverse coating, lip coating, and microgravure coating. Of these, a method of immersing the anode 11 in the conductive polymer dispersion under reduced pressure is preferred. The immersion method allows the conductive polymer dispersion to be sufficiently applied even to the inside of the porous structure on the surface of the dielectric layer 12. After immersion, the anode is removed and subjected to the next drying process.
[0078] Examples of the drying method include room temperature drying, hot air drying, far infrared drying, etc. Among these, hot air drying is preferred. The drying temperature is, for example, preferably 100 to 180° C., and more preferably 120 to 150° C. The drying time is, for example, preferably 0.2 to 1 hour. After drying, the capacitor can be assembled in the usual manner.
[0079] The composition of the components contained in the solid electrolyte layer 14 reflects the composition of the conductive polymer dispersion liquid applied. The content of the polyol compound relative to 100 parts by mass of the polyanion contained in the solid electrolyte layer 14 is, for example, preferably 200 parts by mass or more and 1500 parts by mass or less, more preferably 400 parts by mass or more and 1200 parts by mass or less, and even more preferably 600 parts by mass or more and 900 parts by mass or less. Within the above range, the ESR of the capacitor is reduced and its heat resistance is sufficiently improved.
[0080] The content of the polyol compound relative to 100 parts by mass of the π-conjugated conductive polymer contained in the solid electrolyte layer 14 is, for example, preferably 500 parts by mass or more and 3000 parts by mass or less, more preferably 1000 parts by mass or more and 2500 parts by mass or less, and even more preferably 1500 parts by mass or more and 2000 parts by mass or less. Within the above range, the ESR of the capacitor is reduced and its heat resistance is sufficiently improved.
[0081] <Capacitor> The capacitor comprises an anode made of a porous body of a valve metal, a dielectric layer made of an oxide of the valve metal, a cathode made of a conductive material provided on the dielectric layer opposite the anode, and a solid electrolyte layer formed between the dielectric layer and the cathode, the solid electrolyte layer including a cured product of the conductive polymer dispersion of the second aspect.
[0082] An example of an embodiment of the capacitor will be described with reference to Fig. 1. A capacitor 10 shown in Fig. 1 includes an anode 11 made of a porous body of a valve metal, a dielectric layer 12 made of an oxide of the valve metal, a solid electrolyte layer 14 formed on the surface of the dielectric layer 12, and a cathode 13 provided on the outermost side. The cathode 13 is provided on the opposite side to the anode 11, with the dielectric layer 12 and the solid electrolyte layer 14 sandwiched therebetween.
[0083] Examples of valve metals constituting the anode 11 include aluminum, tantalum, niobium, titanium, hafnium, zirconium, zinc, tungsten, bismuth, and antimony. Among these, aluminum, tantalum, and niobium are preferable. Specific examples of the anode 11 include an aluminum foil that has been etched to increase its surface area and then oxidized, and a tantalum or niobium particle sintered body that has been oxidized and pelletized. Such a processed body is a porous body with irregularities on the surface.
[0084] The dielectric layer 12 in this embodiment is a layer formed by oxidizing the surface of the anode 11, for example, by anodizing the surface of the metallic anode 11 in an electrolyte such as an aqueous solution of ammonium adipate. Similar to the anode 11, the dielectric layer 12 also has projections and recesses.
[0085] The cathode 13 in this embodiment may be a conductive layer formed from a conductive paste or a metal layer made of a conductive material such as aluminum foil.
[0086] The solid electrolyte layer 14 in this embodiment is formed on the surface of the dielectric layer 12. The solid electrolyte layer 14 covers at least a portion of the surface of the dielectric layer 12, and may cover the entire surface of the dielectric layer 12. The thickness of the solid electrolyte layer 14 may be constant or may not be constant, and may be, for example, between 1 μm and 100 μm.
[0087] [Electrolyte] The capacitor may have an electrolyte impregnating a solid electrolyte layer. Examples of the solvent constituting the electrolytic solution include alcohol-based solvents such as ethylene glycol, diethylene glycol, propylene glycol, 1,4-butanediol, and glycerin; lactone-based solvents such as γ-butyrolactone, γ-valerolactone, and δ-valerolactone; sulfur-based solvents such as sulfolane, dimethyl sulfoxide, and dimethyl sulfone; amide-based solvents such as N-methylformamide, N,N-dimethylformamide, N-methylacetamide, and N-methylpyrrolidinone; nitrile-based solvents such as acetonitrile and 3-methoxypropionitrile; and water. Examples of the electrolyte constituting the electrolytic solution include organic acids such as adipic acid, glutaric acid, succinic acid, benzoic acid, isophthalic acid, phthalic acid, terephthalic acid, maleic acid, toluic acid, enanthic acid, malonic acid, formic acid, decanedicarboxylic acids such as 1,6-decanedicarboxylic acid and 5,6-decanedicarboxylic acid, octanedicarboxylic acids such as 1,7-octanedicarboxylic acid, azelaic acid, and sebacic acid; or boric acid, a polyhydric alcohol complex compound of boric acid obtained from boric acid and a polyhydric alcohol; inorganic acids such as phosphoric acid, carbonic acid, and silicic acid as anion components, and primary amines (methylamine, ethylamine, propylamine, butylamine, ethylenediamine, etc.), secondary amines (dimethylamine, diethylamine, dipropylamine, methylethylamine, diphenylamine, etc.), tertiary amines (trimethylamine, triethylamine, tripropylamine, triphenylamine, 1,8-diazabicyclo(5,4,0)-undecene-7, etc.), tetraalkylammonium (tetramethylammonium, tetraethylammonium, tetrapropylammonium, tetrabutylammonium, methyltriethylammonium, dimethyldiethylammonium, etc.), etc., as a cationic component.
[0088] The capacitor is not limited to the above configuration, and may have a separator provided between the dielectric layer and the cathode. An example of a capacitor having a separator provided between the dielectric layer and the cathode is a wound type capacitor. Examples of the separator include sheets (including nonwoven fabrics) made of cellulose, polyvinyl alcohol, polyester, polyethylene, polystyrene, polypropylene, polyimide, polyamide, polyvinylidene fluoride, etc., and nonwoven fabrics of glass fibers. The density of the separator is, for example, 0.1 g / cm 3 More than 1.0g / cm 3 The following are included: When a separator is provided, a method of forming a cathode by impregnating the separator with carbon paste or silver paste can also be applied. EXAMPLES
[0089] (Production Example 1) Production of polystyrene sulfonic acid 1 206 g of sodium styrenesulfonate was dissolved in 1000 ml of ion-exchanged water, and while stirring at 80° C., 1.14 g of an oxidizing agent solution of ammonium persulfate previously dissolved in 10 ml of water was added dropwise over 20 minutes, and the solution was stirred for 12 hours. 1000ml of sulfuric acid diluted to 10% by mass was added to the obtained sodium polystyrene sulfonate solution, and about 1000ml of the solvent from the obtained polystyrene sulfonic acid solution was removed by ultrafiltration. Next, 2000ml of ion-exchanged water was added to the remaining liquid, and about 2000ml of the solvent was removed by ultrafiltration to wash the polystyrene sulfonic acid with water. This washing operation was repeated three times. Water in the obtained solution was removed under reduced pressure to obtain colorless solid polystyrene sulfonic acid (PSS). 10 g of this polystyrene sulfonic acid was dissolved in 90 g of ion-exchanged water to obtain a 10% by mass aqueous solution of polystyrene sulfonic acid.
[0090] The weight average molecular weight (Mw) of the polystyrene sulfonic acid aqueous solution obtained above was measured by gel permeation chromatography (GPC) using pullulan of known weight average molecular weight as the standard substance, and the weight average molecular weight was found to be 200,000.
[0091] The weight-average molecular weight was measured using a Shimadzu Corporation high-performance liquid chromatograph Prominence, with 0.1% NaNO as the solvent. 3 An aqueous solution was used, a Shodex OHpack SB-806M HQ was used as the column, a RID-20A was used as the detector, the solvent temperature was set to 40°C, the flow rate was set to 0.6 ml / min, the PSS concentration in the sample was set to 0.1% by mass, 100 μl of the sample filtered through a membrane filter with a pore size of 0.2 μm was injected, and the analysis was performed using the analysis software Lab Solutions (Shimadzu Corporation).
[0092] (Production Example 2) Production of polystyrene sulfonic acid 2 206 g of sodium styrenesulfonate was dissolved in 1000 ml of ion-exchanged water, and while stirring at 80° C., 0.38 g of an oxidizing agent solution of ammonium persulfate previously dissolved in 10 ml of water was added dropwise over 20 minutes, and the solution was stirred for 12 hours. 1000ml of sulfuric acid diluted to 10% by mass was added to the obtained sodium polystyrene sulfonate solution, and about 1000ml of the solvent from the obtained polystyrene sulfonic acid solution was removed by ultrafiltration. Next, 2000ml of ion-exchanged water was added to the remaining liquid, and about 2000ml of the solvent was removed by ultrafiltration to wash the polystyrene sulfonic acid with water. This washing operation was repeated three times. Water in the resulting solution was removed under reduced pressure to obtain colorless solid polystyrene sulfonic acid. Next, 10 g of the obtained polystyrene sulfonic acid was dissolved in 90 g of ion-exchanged water to obtain a 10% by mass aqueous polystyrene sulfonic acid solution. The weight average molecular weight of the polystyrene sulfonic acid (PSS) obtained above, measured by GPC in the same manner as in Production Example 1, was 540,000.
[0093] (Production Example 3) Preparation of Capacitor Element After connecting an anode lead terminal to the etched aluminum foil (anode foil), a voltage of 40 V was applied in a 10% by mass aqueous solution of ammonium adipate to perform chemical conversion (oxidation treatment) and form dielectric layers on both sides of the aluminum foil to obtain an anode foil. Next, opposing aluminum cathode foils to which cathode lead terminals were welded were laminated on both sides of the anode foil via a cellulose separator, and the resultant was rolled up into a cylindrical shape to obtain a capacitor element.
[0094] Example 1: Preparation of conductive polymer dispersion 5.7 g of 3,4-ethylenedioxythiophene (EDOT), 130.7 g of the polystyrene sulfonic acid (10% by mass aqueous solution) of Production Example 1, 14 g of a 10% by mass aqueous diethylene glycol solution, and 773.6 g of ion-exchanged water were mixed at 25°C. The resulting mixed solution was kept at 25° C., and 19.2 g of a 6% by mass aqueous solution of ferric sulfate was added while stirring. Next, 56.8 g of an 11% by mass aqueous solution of sodium persulfate was added, and the resulting reaction solution was reacted with stirring for 8 hours. By the above reaction, a conductive polymer dispersion liquid was obtained containing poly(3,4-ethylenedioxythiophene), a π-conjugated conductive polymer, a conductive complex (PEDOT-PSS) containing polystyrenesulfonic acid, diethylene glycol, and water as a dispersion medium.
[0095] When the obtained conductive polymer dispersion was analyzed by GPC, the amount of unpolymerized EDOT was below the detection limit.
[0096] To this conductive polymer dispersion, 132 g of Duolite C255LFH (a cation exchange resin manufactured by Sumika Chemtex Corporation) and 132 g of Duolite A368S (anion exchange resin manufactured by Sumika Chemtex Corporation) were added, and the ion exchange resin was removed by filtration to obtain 850 g of a conductive polymer dispersion from which the oxidant and the catalyst had been removed, and the solid content (non-volatile components) was measured. Next, water was removed from the obtained conductive polymer dispersion liquid by distillation under reduced pressure using an evaporator to make the solid content 1.6 mass%. After measuring the viscosity by the method described later, imidazole was added to 100 g of the conductive polymer dispersion liquid to adjust the pH to 2.5, and 8 g of diethylene glycol was further added, and the resulting mixture was used to manufacture a capacitor.
[0097] The capacitor element obtained in Production Example 3 was immersed in the above conductive polymer dispersion liquid under reduced pressure and then dried for 30 minutes in a hot air dryer at 125°C to form a solid electrolyte layer containing a conductive complex on the surface of the dielectric layer. Next, the capacitor element having the above-mentioned solid electrolyte layer formed thereon was loaded into an aluminum case, and the case was sealed with a sealing rubber to prepare a capacitor.
[0098] Example 2 A capacitor was fabricated in the same manner as in Example 1, except that the amount of the 10 mass % diethylene glycol aqueous solution was 28 g and the amount of water was 759.6 g.
[0099] Example 3 A capacitor was fabricated in the same manner as in Example 1, except that the amount of the 10 mass % diethylene glycol aqueous solution was 42 g and the amount of water was 745.6 g.
[0100] Example 4 A capacitor was produced in the same manner as in Example 1, except that the 10% by mass diethylene glycol aqueous solution in Example 1 was replaced with a 10% by mass ethylene glycol aqueous solution.
[0101] Example 5 A capacitor was fabricated in the same manner as in Example 1, except that the 10% by mass diethylene glycol aqueous solution in Example 1 was replaced with a 10% by mass triethylene glycol aqueous solution.
[0102] Example 6 A capacitor was fabricated in the same manner as in Example 1, except that the 10% by mass diethylene glycol aqueous solution in Example 1 was replaced with a 10% by mass propylene glycol aqueous solution.
[0103] Example 7 A capacitor was produced in the same manner as in Example 1, except that the amount of polystyrene sulfonic acid (10% by mass aqueous solution) in Production Example 1 was changed from 130.7 g to 91.3 g, and the amount of water was changed to 813.0 g.
[0104] Example 8 A capacitor was produced in the same manner as in Example 1, except that 130.7 g of polystyrene sulfonic acid (10% by mass aqueous solution, Mw: 200,000) of Production Example 1 was replaced with 130.7 g of polystyrene sulfonic acid (10% by mass aqueous solution, Mw: 540,000) of Production Example 2.
[0105] Comparative Example 1 A capacitor was produced in the same manner as in Example 1, except that the 10 mass % diethylene glycol aqueous solution was not added. Comparative Example 2 A capacitor was produced in the same manner as in Example 7, except that the 10 mass % diethylene glycol aqueous solution was not added. Comparative Example 3 A capacitor was produced in the same manner as in Example 8, except that the 10 mass % diethylene glycol aqueous solution was not added. Comparative Example 4 An investigation was carried out in the same manner as in Example 1 except that polystyrene sulfonic acid was not added. However, particles were precipitated and a conductive polymer dispersion liquid could not be obtained, so the investigation was discontinued.
[0106] Comparative Example 5 5.7 g of 3,4-ethylenedioxythiophene (EDOT), 130.7 g of the polystyrene sulfonic acid (10 mass % aqueous solution) of Production Example 1, and 773.6 g of ion-exchanged water were mixed at 25°C. The resulting mixed solution was kept at 25° C., and 19.2 g of a 6% by mass aqueous solution of ferric sulfate was added while stirring. Next, 56.8 g of an 11% by mass aqueous solution of sodium persulfate was added, and the resulting reaction solution was reacted with stirring for 8 hours. By the above reaction, a conductive polymer dispersion liquid was obtained that contained poly(3,4-ethylenedioxythiophene), which is a π-conjugated conductive polymer, a conductive complex (PEDOT-PSS) containing polystyrenesulfonic acid, and water, which is a dispersion medium. When the obtained conductive polymer dispersion was analyzed by GPC, the amount of unpolymerized EDOT was below the detection limit. To this conductive polymer dispersion, 132 g of Duolite C255LFH (manufactured by Sumika Chemtex Corporation, cation exchange resin) and 132 g of Duolite A368S (manufactured by Sumika Chemtex Corporation, anion exchange resin) were added, and 14 g of a 10 mass % aqueous diethylene glycol solution was added. The ion exchange resin was removed by filtration, and 850 g of a conductive polymer dispersion from which the oxidant and the catalyst had been removed was obtained, and the solid content (non-volatile components) was measured. Next, water was distilled off from the obtained conductive polymer dispersion liquid using an evaporator under reduced pressure to make the solid content 1.6 mass%. After measuring the viscosity by the method described later, imidazole was added to 100 g of the conductive polymer dispersion liquid to adjust the pH to 2.5, and 8 g of diethylene glycol was further added, and the resulting mixture was used to manufacture a capacitor. Comparative Example 6 A capacitor was fabricated in the same manner as in Comparative Example 5, except that the 10% by mass diethylene glycol aqueous solution in Comparative Example 5 was replaced with a 10% by mass ethylene glycol aqueous solution. Comparative Example 7 A capacitor was fabricated in the same manner as in Comparative Example 5, except that the 10% by mass diethylene glycol aqueous solution was replaced with a 10% by mass triethylene glycol aqueous solution.
[0107] [pH measurement] The pH was measured at 25°C by a conventional method using a commercially available pH meter.
[0108] [Method of measuring viscosity] The conductive polymer dispersion with a solid content of 1.6% by mass obtained in each example (however, imidazole and the additional 8 g of diethylene glycol were not added) was dispersed using a high-pressure homogenizer, and the viscosity of the conductive polymer dispersion was measured at 25°C using a tuning fork vibration viscometer (model number: SV-10, manufactured by A&D Corporation) in accordance with JIS Z8803:2011 (viscosity measurement method using a vibration viscometer). 1 Pa s (pascal second) was converted to 1000 cP (centipoise).
[0109] <Evaluation> (Production Example 3) Production of a capacitor The capacitor element was immersed under reduced pressure in the conductive polymer dispersion containing imidazole and diethylene glycol obtained in each example, and then dried for 20 minutes in a hot air dryer at 120°C twice to form a solid electrolyte layer containing a conductive complex on the surface of the dielectric layer. Furthermore, the capacitor element was loaded into an aluminum case and sealed with a sealing rubber to prepare a capacitor.
[0110] [Measurement of capacitance and equivalent series resistance] For the capacitors prepared using the conductive polymer dispersions of each example, the capacitance (unit: μF) at 120 Hz and the equivalent series resistance (ESR) (unit: mΩ) at 100 kHz were measured using an LCR meter ZM2376 (NF Corporation). After measuring the initial ESR, the capacitors were subjected to a heat treatment in which they were left in a thermostatic chamber at 145°C for 300 hours, and the ESR was measured again. The measurement results are shown in Table 1.
[0111] [Table 1]
[0112] From the above, the conductive polymer dispersion produced in the examples according to the present invention has a low viscosity, and the capacitor produced using the conductive polymer dispersion has a low initial ESR, and furthermore, the increase rate of ESR after heat treatment can be reduced. On the other hand, in Comparative Examples 5 to 7 in which a specific polyol compound was not blended during polymerization of the π-conjugated conductive polymer, no reduction in the initial ESR or reduction in the ESR increase rate after heat treatment was observed. From these results, it is understood that the desired effect cannot be obtained even if a specific polyol compound is added later as an additive to the conductive polymer dispersion, and it is important that a specific polyol compound is present during the polymerization reaction of the π-conjugated conductive polymer, i.e., during the formation of the conductive composite. [Explanation of symbols]
[0113] 10 Capacitor 11 Anode 12 Dielectric layer 13 Cathode 14 Solid electrolyte layer
Claims
1. A method for producing a conductive polymer dispersion, comprising: polymerizing a monomer that forms a π-conjugated conductive polymer in a reaction liquid containing a polyanion, a specific polyol compound, and an aqueous dispersion medium, thereby obtaining a conductive polymer dispersion containing a conductive complex containing the π-conjugated conductive polymer and the polyanion, and the polyol compound, the method comprising the steps of: The polyol compound has one or more linear or branched alkylene groups having 2 to 6 carbon atoms and 2 to 3 hydroxyl groups in the molecule.
2. The method for producing a conductive polymer dispersion according to claim 1 , wherein the content of water in the aqueous dispersion medium is 70% by mass or more based on the total mass of the aqueous dispersion medium.
3. The π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene), or the polyanion is polystyrenesulfonic acid, or 3. The method for producing a conductive polymer dispersion according to claim 2, wherein the π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene) and the polyanion is polystyrenesulfonic acid.
4. The method for producing a conductive polymer dispersion liquid according to claim 3 , wherein the polyol compound is at least one selected from the group consisting of ethylene glycol, diethylene glycol, triethylene glycol, and propylene glycol.
5. The method for producing a conductive polymer dispersion according to claim 1 , wherein a content of the polyol compound relative to a total mass of the reaction liquid is 0.01% by mass or more and 0.50% by mass or less.
6. 6. The method for producing a conductive polymer dispersion according to claim 5, wherein a content of the polyol compound is 1 part by mass or more and 100 parts by mass or less with respect to 100 parts by mass of the polyanion contained in the reaction liquid.
7. The method for producing a conductive polymer dispersion according to claim 6 , wherein a content of the polyol compound relative to 100 parts by mass of the monomer contained in the reaction liquid is 1 part by mass or more and 100 parts by mass or less.
8. A method for producing a capacitor, comprising the steps of: obtaining a conductive polymer dispersion by the production method according to any one of claims 1 to 7; and applying the conductive polymer dispersion to a surface of a dielectric layer formed on a surface of an anode made of a porous body of a valve metal, and drying the conductive polymer dispersion to form a solid electrolyte layer.
9. 9. The method for producing a capacitor according to claim 8, wherein a content of the polyol compound is 200 parts by mass or more and 1500 parts by mass or less with respect to 100 parts by mass of the polyanion contained in the solid electrolyte layer.
10. 10. The method for producing a capacitor according to claim 9, wherein a content of the polyol compound is 500 parts by mass or more and 3000 parts by mass or less with respect to 100 parts by mass of the π-conjugated conductive polymer contained in the solid electrolyte layer.
Citation Information
Patent Citations
Polymeric composite for conductive film, and production method and use of the same
JP2012224721A
Conductive polymer-containing solution, method for producing the same, and method for producing conductive film
JP2020007470A
Manufacturing method of positive electrode for capacitor, and manufacturing method of capacitor
JP2021190654A
Method for producing conductive polymer and method for producing solid electrolyte capacitor
WO2014017098A1
Capacitor and manufacturing method thereof
JP2022071400A